A bundler prototype for forestry and agricultural residue management for energy production. Issue 2 (3rd May 2016) - Manzone, Marco
ABSTRACT: In recent years, a large amount of wood biomass has been produced for energy use by the agricultural and forestry sectors. The goal of this study was to set up a chip bundler prototype which can work with different feedstocks (agricultural and forestry residues). During tests, the prototype was able to produce bundles with a weight between 18 and 20 kg requiring an energy input of between 0.54 and 0.58 MJ kg −1, respectively. The production cost of a single bundle was €2.43, independent of the loading type (mechanical or manual) adopted. The bundler tested seems ideal for the agro-forestry sector because it shows a high versatility: the form and size of the biomass processed does not interfere with productivity or cost. In addition, the prototype requires a small amount of power and a small investment. Because of these reasons, the bundler can be used by individual farmers and small businesses.